Exploring the Strengths and Weaknesses of Teaching Speaking by Using LMS-Edmodo - Rifki Irawan (Journal of English Language Teaching and English Linguistics, 2020)
The aim of this research is to explore the strengths and weaknesses of teaching speaking by using LMS-Edmodo based on the teacher’s perceptions. This research is a qualitative descriptive approach that involved one teacher as a participant. Observation, documentation, and interview are three kinds of instruments which were applied to this research. The data were collected by using three stages of qualitative analysis (Miles & Huberman, 1994), which were data reduction, data display, and conclusion drawing and verification. Based on the teacher’s perception, the strengths of teaching speaking by using Edmodo are its economy, privacy, simplicity, and flexibility. On the other hand, time-consuming, harm to the teacher’s health, slow loading if The aim of this research is to explore the strengths and weaknesses of teaching speaking by using LMS-Edmodo based on the teacher’s perceptions. This research is a qualitative descriptive approach that involved one teacher as a participant. Observation, documentation, and interview are three kinds of instruments which were applied to this research. The data were collected by using three stages of qualitative analysis (Miles & Huberman, 1994), which were data reduction, data display, and conclusion drawing and verification. Based on the teacher’s perception, the strengths of teaching speaking by using Edmodo are its economy, privacy, simplicity, and flexibility. On the other hand, time-consuming, harm to the teacher’s health, slow loading if lacks of internet connection, the error of the system, easy for students to copy and paste their classmates’ assignments are its weaknesses.